Jump rope games as a medium for gross motor development in early childhood - Asnita; Agusniatih, Andi; Awalunisah, Sita (Universitas Islam Negeri Raden Intan Lampung, 2025)
Background: Early childhood education (ages 3–6 years) is known as a golden developmental period that requires appropriate stimulation to optimize all developmental domains, including gross motor skills. Observations conducted at TK Mololisan Rano Balaesang Tanjung revealed that children’s gross motor abilities had not yet developed as expected, as indicated by weak balance, strength, and agility due to limited physical activity. One potentially effective solution is the use of traditional physical play, such as jump-rope games, which stimulate gross motor performance. Objective: This study aims to examine the influence of jump-rope play activities on the gross motor skills of children in Group A. Method: This research employed a quantitative descriptive design. The study involved 10 children (3 boys and 7 girls) who participated in the program for three weeks. Data were collected through observation, documentation, and interviews, then analyzed using descriptive statistics and inferential testing with a t-test. Results: The findings indicate that jump-rope play had a significant effect on improving children’s gross motor abilities, particularly in the aspects of balance, agility, and coordination. Conclusion: Jump-rope activities may serve as an enjoyable learning medium that effectively supports the development of gross motor skills in early childhood.